2016
DOI: 10.1051/0004-6361/201628302
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the origin of the radio emission in radio-quiet quasars

Abstract: The origin of the radio emission in radio-quiet quasars (RQQs) has been a matter of debate for a long time. It is not well understood whether the emission is caused by star formation in the host galaxy or by black hole activity of the active galactic nuclei (AGN). We shed some light on these questions using the Very Long Baseline Interferometry (VLBI) technique to search for RQQs in the field of the Cosmological Evolution Survey (COSMOS). The extensive multi-wavelength coverage of the field (from radio to X-ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 39 publications
3
51
0
Order By: Relevance
“…Such cores can account for a significant fraction of the total radio emission (up to ∼70% in RQ76). Although limited in a statistical sense, our findings are supported by similar results by Herrera Ruiz et al (2016), who found VLBI cores in RQ QSOs in the COSMOS field. Further support comes from the 12 RQQ sources (according to the classification of Bonzini et al 2013) observed by Chi et al (2013), four of which were detected with VLBI.…”
Section: Discussionsupporting
confidence: 91%
“…Such cores can account for a significant fraction of the total radio emission (up to ∼70% in RQ76). Although limited in a statistical sense, our findings are supported by similar results by Herrera Ruiz et al (2016), who found VLBI cores in RQ QSOs in the COSMOS field. Further support comes from the 12 RQQ sources (according to the classification of Bonzini et al 2013) observed by Chi et al (2013), four of which were detected with VLBI.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies based on interferometric radio observations of sub-mJy radio sources have the potential to shed light on this issue. For example, Herrera Ruiz et al (2016) analysed in detail the interferometric images of three RQ-AGN obtained with VLBI in the COSMOS field, which are part of the sample described in Sect. 4.3.1.…”
Section: Radio Emission In Hlagn and Mlagnmentioning
confidence: 99%
“…High-resolution (milli-arcsec) radio observations by Jackson et al (2015), Maini et al (2016) and Herrera-Ruiz et al (2016) have revealed that RQ AGNs can contain nuclear radio cores significantly contributing to the total radio emission. On a larger statistical ground, deep sub-arcsec resolution radio observations of the GOODS-N field have revealed that RQ AGNs are preferentially associated to more compact radio emission than starforming galaxies (Guidetti et al 2017).…”
Section: Introductionmentioning
confidence: 99%